2021
DOI: 10.3390/cancers13040724
|View full text |Cite
|
Sign up to set email alerts
|

SILAC-Based Quantitative Proteomic Analysis of Oxaliplatin-Resistant Pancreatic Cancer Cells

Abstract: Oxaliplatin is a commonly used chemotherapeutic drug for the treatment of pancreatic cancer. Understanding the cellular mechanisms of oxaliplatin resistance is important for developing new strategies to overcome drug resistance in pancreatic cancer. In this study, we performed a stable isotope labelling by amino acids in cell culture (SILAC)-based quantitative proteomics analysis of oxaliplatin-resistant and sensitive pancreatic cancer PANC-1 cells. We identified 107 proteins whose expression levels changed (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Here, we found that substantial increases in the levels of MARCKS expression and activating phosphorylation were correlated with elevated WNT5A expression and increased invasion and migration of BRAFi-R melanoma cells. Previous studies performed in pancreatic and hematological cancers have also revealed increased MARCKS expression and MARCKS phosphorylation in cancer cells that have developed resistance to drugs such as oxaliplatin and proteasome inhibitors [ 57 , 58 , 59 , 60 ]. However, none of the aforementioned studies were directed toward exploring whether and how the MARCKS protein contributes to the increased invasion and migration of drug-resistant cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that substantial increases in the levels of MARCKS expression and activating phosphorylation were correlated with elevated WNT5A expression and increased invasion and migration of BRAFi-R melanoma cells. Previous studies performed in pancreatic and hematological cancers have also revealed increased MARCKS expression and MARCKS phosphorylation in cancer cells that have developed resistance to drugs such as oxaliplatin and proteasome inhibitors [ 57 , 58 , 59 , 60 ]. However, none of the aforementioned studies were directed toward exploring whether and how the MARCKS protein contributes to the increased invasion and migration of drug-resistant cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Evi/Wls has been suggested to be used as a biomarker for Wnt expression and for disease progression in cancers affecting breast, liver, pancreas, gastrointestinal tract, brain, bone and prostate ( Table 1 ). Using Evi/Wls as a biomarker could help to predict therapy resistance, to identify individuals for Wnt-targeting therapy or to identify the tissue of origin ( Augustin et al, 2012 ; Bland et al, 2021 ; Chua et al, 2021b ; Kim et al, 2021 ; Ma et al, 2022 ; Seo et al, 2018a , b ; Shi et al, 2018 ; Shuai et al, 2021 ; Zheng et al, 2020 ; Zhou et al, 2018 ). For example, Ma and colleagues recently treated a mouse model created using a Evi/Wls-positive pancreatic cancer patient-derived xenograft with Porcupine inhibitors and thus reduced tumour growth ( Ma et al, 2022 ).…”
Section: Monitoring and Manipulating Wnt Export: Evi/wls As A Biomarkermentioning
confidence: 99%
“…However, emerging marking techniques such as chemical labeling and labeling with stable isotopes contribute to make MS an accurate quantitative technique [81]. The main quantitative proteomic methods involve the following techniques: isotope-coded affinity tag (ICAT) labeling [82], stable isotope labeling with amino acids in cell culture (SILAC) [83,84], and isobaric tag for relative and absolute quantitation (iTRAQ) [85].…”
Section: Mass Spectrometrymentioning
confidence: 99%